Lipid metabolism in age-related musculoskeletal disorders: insights into sarcopenia and osteoporosis - Shivum Lal; Shreya Gunji; Pankaj Ahluwalia; Ravindra Kolhe; Wendy B. Bollag; William D. Hill; Meghan E. McGee-Lawrence; Carlos M. Isales; Sadanand Fulzele (BMC Biology)
Abstract Musculoskeletal disorders (MSDs), notably sarcopenia and osteoporosis, profoundly affect aging individuals. This review explores lipid metabolism's role in age-related MSD pathophysiology, highlighting fatty acid uptake, lipid signaling, and lipotoxicity in muscle deterioration. It further addresses lipid-mediated regulation of osteoclasts, osteoblasts, and bone remodeling, emphasizing age-associated metabolic shifts exacerbating bone loss. Emerging therapeutic strategies targeting lipid pathways for MSD treatment are also discussed. This review integrates recent findings in muscle and bone lipid metabolism to deepen understanding of lipid dysregulation in musculoskeletal disorders and explore potential metabolic intervention strategies.